The Selection of Eco-Friendly Tuna Fishing Technology (Euthynnus affinis) at Fish Landing Bases (PPI) Kuala Langsa Aceh Province - Muhammad Zikri Imanullah; Bustari Bustari; Arthur Brown (Jurnal Perikanan dan Kelautan, 2024)
This study aims to identify and determine environmentally friendly tuna fishing gear and the priority for developing fishing gear at PPI Kuala Langsa. The method used in this research is a survey method. Moreover, purposive sampling was chosen as a sampling technique in selecting respondents as the sample. The data obtained were processed using the scoring and analytical hierarchical processes (AHP) methods. Based on the eco-friendly level, the longline scored 82.71%, the surface gill net scored 79.38%, the bottom gill net scored 76.04%, and the purse seine scored 74.79%. Based on the results of the AHP analysis, the fishing gears that became the main priority were longline with a value of 0.311, purse seine with a value of 0.293, surface gill nets with a value of 0.220, and bottom gill net with a value of 0.176. The government must reoptimise the catch of tuna based on environmentally friendly criteria. Also, it is necessary to conduct further research related to environmentally friendly fishing gear for other types of fish, and it is necessary to apply regulations regarding environmentally friendly fishing gear.